(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Conservation of endemic rare-threatened plants and sustainable exploitation of biodiversity with emphasis on medicinal-aromatic plants and plants with horticultural/ornamental value can be achieved through ex situ conservation activities. For this purpose, propagation experiments with cuttings were performed on four local Ionian endemic species with conservation priority, Stachys ionica Halácsy, Teucrium halascyanum, Thymus holosericeus Celak and Thymus plasonii Adamovic (all Lamiaceae). For propagation, softwood tip cuttings (3-5 cm) were cut at early autumn from mother plants collected from the wild and maintained in open-air mother plantations. For experimentation, the base of cuttings was immersed for 1 min in solutions of four concentrations of IBA (0, 1000, 2000 and 4000 ppm). Cuttings were placed on a peat:perlite (1:3) substrate in the bench of greenhouse heated mist system. Most suitable treatment for T. halascyanum (3 ½ weeks) proved to be 1000 ppm IBA (32.13 roots 1.72 cm long, 100% rooting). Accordingly, 2000 ppm IBA gave 100% rooting for both S. ionica (28.5 roots 1.56 cm long,) (3 weeks) and Th. holosericeus (4.4 roots 1.76 cm long) (7 weeks). T. plasonii cuttings treated with 2000 ppm IBA gave 85.71% optimum rooting with 8.67 roots 1.78 cm long.